Collaborative Governance Sebagai Alternatif Pemerintah Daerah dan Perseroan Dalam Mengatasi Permasalahan Sektor Pertambangan: Studi Program TJSL Tambang Galian C PT. AMS di Kabupaten Banyuwangi - Holqi, Fikri Gali Fernando; Salam, Abdus (Universitas Indo Global Mandiri, 2024)
Mining activities always provide negative potential in environmental and social aspects. This can be identified in the emergence of community opposition to mining activities. To reduce this, mutually beneficial handling between the Company and the Community is needed, Thus, local governments have a role to create good and mutually beneficial relationships through Collaborative Governance policies. This study seeks to identify the concept of Collaborative Governance carried out in the implementation of the TJSL program at the C Quarry in Banyuwangi Regency through relations between local governments, mining companies, and civil society. Implementing a qualitative approach with the type of case study. Primary data contains observations, interviews, and documentation. Secondary data contains findings in journals, books, and other literature. The results of the study stated that Collaborative Governance in the mining sector carried out through the implementation of the TJSL program at the C Quarry in Banyuwangi Regency involved several stakeholders including the Ministry of Energy and Mineral Resources, the Banyuwangi Regional Government, the Environmental Agency, Mining Companies, and Community Leaders. The mining company actualizes the TJSL principle which is carried out by implementing several programs, namely by contributing material funds to each hamlet allocated to the realm of places of worship, besides that the company is also responsible for all damage that occurs as a result of the activities of highly loaded mining trucks to road infrastructure, as well as sirtu mining material products allocated to community needs as building materials, thus creating a mutually beneficial relationship.